Necessary actions for the solution of inequality in labor law opportunities (GnosisWisdom, 2023)
The objective of this article is to make known the advances of equal opportunities in labor law, in the same way to know different conceptions and theoretical constructions that one has of it, since it is known that at present the countries that consider and practice equality develop greater economic and social growth and obtain a tomorrow of well-being with quality of life for future generations, considering that equal opportunities more than a right is an objective of progress, therefore it is necessary to incorporate measures and actions so that In this way, more job opportunities are formed and can be created for everyone, building fairer conditions at work, because protection against inequality is a fundamental human right and it is very important because thanks to this, workers can freely select their work or work and in this way they can fully develop their potential and benefit from their efforts based on their merits, in this sense the need to create alternative models with the necessary actions to build a society that contemplates a vision and an equitable approach is demanded. , equal and fair.
Keywords: labor law; equality; progress; inequality; fair